High frequency repetitive transcranial magnetic stimulation versus sertraline in treatment of poststroke depression: A pilot study - Terachinda, Pim; Tantanatip, Anuphan; Piravej, Krisna; Tangwongchai, Sookjareon; Srioum, Sunisa; Sillapachai, Thipwimon; Hongsachat, Pisamai; Chongpison, Yuda (Chulalongkorn Medical Journal, 2021)
Background: Poststroke depression (PSD) has impact on rehabilitation outcome. Repetitive transcranial magnetic stimulation (rTMS) has been proven as a treatment of depression and might reduce depressive symptoms after stroke. Objectives: To determine the effects of high frequency rTMS in treatment of PSD compared to sertraline. We also investigated the effects of rTMS combined with sertraline. Methods: Fourteen patients with PSD were randomly allocated into 3 groups: 1) the rTMS group received 10 sessions of 10 Hz rTMS; 2) the sertraline group obtained sertraline 50 mg daily and sham rTMS; and, 3) the combined group received 10 Hz rTMS combined with sertraline 50 mg daily. Hamilton rating scale for depression (HAM-D) was assessed at baseline and week 2, 6 and 14. At baseline and week 6 and 14, modified Barthel Index (MBI) and Brunnstrom stages of stroke recovery were evaluated. Results: The rTMS group showed significant reduction of HAM-D score at week 6 (- 9.8 7.1; P < 0.05) while the sertraline and combined groups did not show significant improvement (- 9.2 1.0 and - 4.8 2.9, respectively). HAM-D, response and remission rate, response and remission over the time, MBI and motor recovery among groups were not significantly different. Conclusion: High frequency rTMS might have antidepressant effect in PSD. Its effect might not be different from sertraline. Benefit of rTMS given in combination with sertraline over rTMS or sertraline alone is still inconclusive.